New Image Painting - Marshall, Richard (New York : Whitney Museum of American Art, 1978)
Africano, Nicholas ; Bartlett, Jennifer ; Green, Denise ; Hurson, Michael ; Jenney, Neil ; Lane, Lois ; Moskowitz, Robert ; Rothenberg, Susan ; True, David ; Zucker, Joe
New Image Painting, Whitney Museum of American Art, New York, December 5, 1978 - January 28, 1979
boek